URGENSI CYBER LAW DALAM MENJAGA PRIVASI PASIEN DI RUMAH SAKIT ERA DIGITAL - Hana Nur Hanifah; Irawati, Arista Candra (ADIL Indonesia Journal, 2024)
In the digital era, cyber crime has become one of the biggest problems in Indonesia, especially in hospital environments. The security and privacy of patient data in hospitals is an example of a very important aspect in the digitalization era. Implementing Cyber ​​Law is the key to protecting sensitive patient data from the threat of data theft, illegal access and information leakage. This article discusses the application of Cyber ​​Law in the hospital environment, including the protection of patient data which is regulated in several laws, such as Law Number 8 of 1999 concerning consumer protection, Law Number 29 of 2004 concerning medical practice, Law Number 44 of 2009 concerning Hospitals to Law Number 19 of 2016 concerning electronic information and transactions (ITE).This research uses a qualitative method with a descriptive approach, analyzing how existing legal policies are implemented to maintain the confidentiality of patient data. The research results show that even though regulations are available, challenges such as a lack of understanding of the law by health workers, limited technological infrastructure, and the threat of cyber attacks are still the main challenges. Therefore, there is a need to increase education, strengthen security systems in each hospital, and collaborate between stakeholders to ensure patient data is protected in accordance with legal principles and medical ethics.   ABSTRAK Di era digital, kejahatan siber telah menjadi salah satu masalah terbesar yang ada di Indonesia terutama di lingkungan rumah sakit. Keamanan dan Privasi data pasien di rumah sakit merupakaan salah satu contoh aspek yang sangat penting dalam era digitalisasi. Implementasi Cyber Law menjadi kunci untuk melindungi data sensitive pasien dari ancaman pencurian data, akses illegal, dan kebocoran informasi. Artikel ini membahas penerapan hukum Cyber Law di lingkungan rumah sakit, termasuk perlindungan data pasien yang diatur dalam beberapa UU, seperti Undang-undang Nomor 8 Tahun 1999 tentang perlindungan konsumen, Undang-undang Nomor 29 Tahun 2004 tentang praktik Kedokteran, Undang-undang Nomor 44 Tahun 2009 tentang Rumah sakit hingga UU Nomor 19 Tahun 2016 tentang informasi dan transaksi elektronik (ITE). Penelitian ini menggunakan metode Kualitatif dengan Pendekatan deskriptif, menganalisis bagaimana kebijakan hukum yang ada diimplementasikan untuk menjaga kerahasiaan data pasien. Hasil penelitian menunjukan bahwa meskipun regulasi tersedia, tantangan seperti kurangnya pemahaman hukum oleh tenaga Kesehatan, keterbatasan infrastruktur teknologi, dan ancaman serangan siber masih menjadi hambatan utama. Oleh karena itu, perlu peningkatan edukasi, penguatan sistem keamanan di setiap rumah sakit, dan kolaborasi antar pemangku kepentingan untuk memastikan data pasien terlindungi sesuai dengan prinsip hukum dan etika medis.